Social Media, Family Relations, and the Millennial Generation: A Hadith Review - Achmad Ghozali Syafi’i; Suardi Suardi; Ahmat Saepuloh; Artis Artis; Rahman Rahman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine the impact of social media on millennial family relationships from the perspective of the Prophet’s hadith. The background of this research is grounded in the rapid development of social media, which has significantly transformed patterns of interaction and communication within families. Social media provides easy access to information and expands connectivity among family members; however, it also presents challenges, including the decline in the quality of face-to-face interaction, the weakening of emotional bonds, and shifts in moral and ethical values within household life. This research employs a qualitative approach using thematic (maudhu‘i) analysis. A number of hadith related to family harmony, communication ethics, responsibility, time management, and moral development are analyzed descriptively and analytically to identify normative principles relevant to the digital context. The findings indicate that the Prophet’s teachings emphasize the principle of balance (wasatiyyah), collective responsibility within the family, and the importance of ethical communication as the foundation of family resilience. Hadith concerning guarding one’s speech, managing time proportionally, and prioritizing family obligations remain contextually relevant in the era of social media. In conclusion, social media should be positioned as a supportive tool for family harmony rather than a disruptive factor, provided its use is guided by ethical and spiritual values rooted in the Prophet’s teachings.